Case Report of a Neonate Born to a Mother with Severe SARS-CoV-2 Infection under ECMO - Vilardouro, Ana Sofia (2022)
Neonatal SARS-CoV-2 infections are rare and although there is some evidence of vertical transmission, most newborns show no clinical signs or present with only mild clinical symptoms. Fetal survival is reported around 70% in mothers submitted to extracorporeal membrane oxygenation. We present a case of a male newborn born at 29 weeks from a mother under extracorporeal membrane oxygenation due to SARS-CoV-2 infection. There was no evidence of vertical transmission, polymerase chain reaction testing of nasopharyngeal/throat swab and polymerase chain reaction testing of blood sample for SARS-CoV-2 were both negative. On day 2, he developed signs of osteomyelitis of the distal femur extremity, which resolved after six weeks of antibiotic therapy, with no other significant events during admission. This case report depicts the favorable outcome of a live infant born to a mother with severe SARS-CoV-2infection under extracorporeal membrane oxygenation.